2005
DOI: 10.1159/000083636
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha Activates MUC2 Transcription via NF-kappaB but Inhibits via JNK Activation

Abstract: The molecular mechanisms responsible for TNF-α-mediated MUC2 intestinal mucin up-regulation in HM3 colon adenocarcinoma cells were analyzed using promoter-reporter assays of the 5’-flanking region of the MUC2 gene. Chemical inhibitors, mutant reporter constructs, and EMSA confirmed I-kappaB/NF-kappaB pathway involvement. Wortmannin, LY294002 and dominant negative Akt, as well as dominant negative NF-kappaB-inducing kinase (NIK) inhibited MUC2 reporter transcription, indicating that both phosphatidylinositol-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 40 publications
5
58
1
Order By: Relevance
“…MUC2 is a secreted mucin than can be regulated through different pathways such as MAPK, NF-kB and Ras/MEK in colon cancer cells (Lee et al, 2002;Kim et al, 2004;Ahn et al, 2005). Muc2 À/À mice present increased proliferation and migration and decreased apoptosis of intestinal epithelial cells and develop spontaneous tumors that progress to invasive carcinomas, suggesting a role for Muc2 in tumor suppression (Velcich et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…MUC2 is a secreted mucin than can be regulated through different pathways such as MAPK, NF-kB and Ras/MEK in colon cancer cells (Lee et al, 2002;Kim et al, 2004;Ahn et al, 2005). Muc2 À/À mice present increased proliferation and migration and decreased apoptosis of intestinal epithelial cells and develop spontaneous tumors that progress to invasive carcinomas, suggesting a role for Muc2 in tumor suppression (Velcich et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…6,8 We showed that LPSinduced CDX2 and MUC2 mRNA expression in cultured BECs disappeared on transfection of CDX2 siRNA, and that forced expression of CDX2 by using the CDX2 expression vector upregulated MUC2 expression in cultured BECs, supporting reports that CDX2 exists upstream of MUC2 and activates transcription of MUC2. 6,8 However, it is also known that MUC2 has NF-kB-binding sites in the promoter region, 32,36 and the activation of NF-kB could directly trigger Intestinal metaplasia of bile ducts H Ikeda et al MUC2 expression. In fact, MG132, an inhibitor of NF-kB, inhibited CDX2 mRNA expression and also MUC2 mRNA expression in this study (Figure 7a).…”
Section: Intestinal Metaplasia Of Bile Ducts H Ikeda Et Almentioning
confidence: 99%
“…For example, the balance between NF-nB and JNK activity controls dendritic cell survival (17). JNK inhibition results in NF-nB activation in multiple myeloma cell lines (18), and NF-nB activation induces MUC2 transcription whereas JNK activation inhibits this induction in human colon epithelial cells (19). Previously, we found that induction of intestinal cell differentiation is associated with increased JNK activity and c-Jun phosphorylation (20).…”
Section: Introductionmentioning
confidence: 98%